ANALISA MATERIAL BALANCE UNTUK SUMUR GAS MENGGUNAKAN DATA TEKANAN ALIR DASAR SUMUR - Priatmojo M, Sandro
The P/z method has been widely used in determining in place in gas reservoir. This method requires reservoir pressures after shutting the well. After production, shutting the well is really avoided because the well can be off when it wants to be produced again. Because of that, the data are not often available in the field. As alternative, even it is not correct analytically and less accurate, it is used bottom hole flowing pressure or called Pwf. In this study, it is analyzed the limitation of method Pwf/z can be used and also defined as an equation approach to determine the true in place from this method. The result of this Final Test is this method is applicable in condition gas saturation > 0.8, permeability > 40 md, and initial pressure < 3000 psia. For high initial pressure or low permeability condition, it can be used an equation proposed in this Final Test.